Signifikansi Pengaruh Akses Teknologi Informasi terhadap Indeks Pembangunan Manusia di Indonesia - Andriyan Rizki Jatmiko; Nofrian Deny Hendrawan; Rizza Muhammad Arief; Firnanda Al Islama Achyunda Putra; Mochammad Daffa Putra Karyudi (Universitas Harapan Medan, 2023)
Human Development Index is an indicator of the progress of a country, Information Technology is an important supporter to measure the Human Development Index. This research can provide an overview to measure the progress of a country in terms of access to Information Technology. This study processed secondary data provided by the Central Statistics Agency from 2017-2019. Using K-Means and K-Medoids clustering methods. K-Means is a popular non-hierarchical grouping method that groups objects by distance to a central point, aiming to maximize similarity within groups. K-Medoids is a powerful algorithm that handles outliers using techniques such as CLARA and PAM. In 2017 with an average of 0, Gorontalo 294611827 was a low cluster while in 2018 and 2019 Gorontalo entered a medium cluster with an average of 0.349570215 and 0.394531648. Similar to Central Sulawesi, in 2017 with an average of 0.275848883 Central Sulawesi was included in the low cluster while in 2018 and 2019 Central Sulawesi entered the medium cluster with an average of 0.291938731 and 0.334276807 From this result, it can be ascertained, by increasing knowledge in Information Technology, the HDI in an area can increase as well.